Supra- and Subgingival Microbiome in Gingivitis and Impact of Biofilm Control: A Comprehensive Review - Margarita Iniesta; Viviane Vasconcelos; Mariano Sanz; David Herrera (MDPI AG, 2024)
This comprehensive review aimed (1) to characterize the sub- and supragingival microbiome in patients with biofilm-induced gingivitis (including experimental gingivitis), (2) to assess its stability and evolution over time, and (3) to assess the impact of biofilm control measures on this stability. An electronic search of the MEDLINE®/PubMed® database until December 2023 was conducted. NCBI Taxonomy, eHOMD 16S rRNA Reference Sequence, and Tree Version 15.23 databases were used to standardize taxonomic nomenclature. Out of 89 papers initially retrieved, 14 studies were finally included: 11 using experimental gingivitis as a model and three randomized clinical trials evaluating the impact of biofilm control measures. Among them, five characterized the subgingival microbiome, nine the supragingival microbiome, and one both the sub- and supragingival microbiome. In addition, five studies evaluated the effect of toothpaste, and four studies evaluated the effect of mouth rinses. The diversity and structure of the microbiome differed significantly between patients with periodontal health and those with biofilm-induced gingivitis (including experimental gingivitis). Those differences were not reversed through conventional oral hygiene measures. Specific antiseptic agents, especially if delivered as mouth rinses, may have an impact on the supra- and subgingival microbiome in gingivitis.